Space arrangement and accessibility Impact of the Iraqi traditional courtyard House: an investigation of two case studies in Iraq, Baghdad - Shakir Haraty, Hayder Jawad; Mat Raschid, Mohammad Yazah; Mohd Yunos, Mohd Yazid (Science Publishing Corporation, 2019)
Spatial arrangement and components of the traditional Iraqi courtyards house have been utilized to express the residence activities inside the house and controlled their privacy. Despite its rich social content, the importance of those traditional house has been forgotten due to the rapid construction in Iraqi development. The lack of understanding on the meaning of the courtyards houses has led to a considerable gap between the current and the traditional housing resulting in an imperative need of urgent investigation of the issue. The study investigates how the Iraqi traditional courtyard house functioned and served both as a social and cultural place for the family and the guests activities. The two case studies of traditional Iraqi courtyard houses in Baghdad; in Al-Kadhymia district, were selected and morphologically analysed in this study. Floor plans and drawings of each case study were utilized to understand the physical planning of the traditional courtyard houses. The study concludes that the traditional courtyards have indirectly influenced the local people socially and culturally. The courtyard are utilized for various socially connected activities relating to the unit residential family and guests creating a more hospitable environment for interactions and better lifestyle. This study notably fills the gap in the design of the contemporary housing in Iraq and can be further expand to regional area.